Identification of Putative Cell‐entry‐inhibitory Peptides against SARS‐CoV‐2 from Edible Insects: An in silico Study. Issue 5 (25th September 2020) - Wong, Fai‐Chu; Ong, Joe‐Hui; Chai, Tsun‐Thai
Abstract : Coronavirus Disease 2019 (COVID‐19), an infectious disease caused by SARS‐CoV‐2, has become the most contagious pandemic in the world. The binding of SARS‐CoV‐2 spike glycoprotein Receptor‐binding Domain (RBD) to human angiotensin‐converting enzyme 2 receptor precedes cell entry. Thus, RBD of SARS‐CoV‐2 spike glycoprotein is a key target for the development of drugs and vaccines to curb COVID‐19. The aim of this in silico study was to identify potential SARS‐CoV‐2 cell entry inhibitors from peptides derived from edible insects. Twenty‐four major proteins from mealworms, silkworm cocoons and housefly larvae were subjected to in silico gastrointestinal (GI) digestion, yielding 3560 fragments. Further screening led to 82 high‐GI‐absorption peptides with unique sequences. Molecular docking revealed 10 promising peptides (VPW, PPY, PIF, VW, PSF, PGF, PAY, VGF, PF and TW), predicted to interact with at least one key binding residue on RBD. Notably, VPW had the lowest docking energy score (−144.359) and binding affinity (−7.0 kcal/mol), highlighting its potency among the ten peptides. Binding affinities of the insect peptides were superior to some reported natural products. Our study suggests that when consumed, edible insects may be a source of putative SARS‐CoV‐2 cell entry inhibitors in the form of RBD‐binding peptides. GRAPHICAL ABSTRACT: